Comparing the Effectiveness of Cognitive Behavioral Therapy and Emotion-Focused Therapy on Mindfulness and Psychological Flexibility in Generalized Anxiety Disorder - Alireza Ahangaran; Fathi, Hasan; Azimi, Negin Sadat; Ghorbani, Aliyeh (Health Nexus, 2026)
This study compared the effectiveness of cognitive behavioral therapy (CBT) and emotion-focused therapy (EFT) for improving mindfulness and psychological flexibility in women with generalized anxiety disorder (GAD). A quasi-experimental pretest-posttest design with a control group and follow-up assessment was used. Forty-five women with GAD who attended counseling and psychological service centers in Tehran in 2025 were selected through purposive sampling and then randomly assigned to three groups (n = 15 per group): CBT, EFT, and control. Interventions were delivered online in 12 weekly 90-minute sessions. Measures included the Generalized Anxiety Disorder Scale (GAD-7), the Five Facet Mindfulness Questionnaire (FFMQ-15), and the Acceptance and Action Questionnaire-II (AAQ-II). Data were analyzed using repeated-measures analysis of variance in SPSS version 26. Both active treatments produced significant improvements compared with the control group, but CBT showed the strongest effects. For mindfulness, the CBT group increased from M = 31.46 (SD = 5.12) at pretest to M = 54.06 (SD = 5.00) at posttest and M = 55.53 (SD = 8.41) at follow-up, whereas the EFT group increased from M = 32.73 (SD = 4.51) to M = 47.73 (SD = 4.72) and M = 47.20 (SD = 4.75). For AAQ-II scores, where lower scores indicate greater psychological flexibility, the CBT group improved from M = 33.80 (SD = 3.23) to M = 17.60 (SD = 4.08) and M = 18.26 (SD = 4.31), while the EFT group improved from M = 36.06 (SD = 3.43) to M = 23.40 (SD = 3.45) and M = 22.93 (SD = 4.69). The repeated-measures ANOVA showed significant time, group, and time × group effects for both mindfulness and psychological flexibility (all p < .001). Both CBT and EFT were effective in women with GAD, but CBT yielded greater gains in mindfulness and psychological flexibility and maintained these gains at follow-up.